Adaptation of Ohia Pozzolan on Cemented Lateritic Soil as Base Material Improvement - K.C. Onyelowe (International Association of Lowland Technology, 2019)
The effect of nanostructured Ohia naturally occurring pozzolan (kaolin clay) on the compressive strength of Umuntu Olokoro lateritic soil was investigated for use as base material improvement of south eastern roads. First, a preliminary exercise was conducted to determine the index, grading and consistency properties of the natural soil. The results show that the Umuntu Olokoro soil was an A-2-7 soil, according to AASHTO classification system and poorly graded (GP) on USCS classification. The soil also recorded a PI of 21.85%, which shows that the soil was highly plastic. The specific gravity of the soil was 2.67, OMC of 13%, Maximum Dry Density of 1.84 gm/cm3, California Bearing Ratio of 14%, Unconfined Compressive Strength of 194.26 kN/m2, 219.11 kN/m2 and 230.77 kN/m2 at 7, 14 and 28 days curing periods with material property of silty clayey sand and stiff material. Furthermore, the pozzolan additive was introduced in proportions of 3%, 6%, 9%, 12% and 15% by weight and the effect of the varying proportions studied. The results show that the introduction of the pozzolan improved the soil compressive strength, considerable and a maximum of 369.9 kN/m2 was achieved at 9% proportion of pozzolan at 28 days curing time. Having satisfied the material properties for use as a base material (200-400kN/m2), pozzolan is a very good admixture material in the stabilization of lateritic soils for use as a subbase material for pavement construction.